2021
DOI: 10.1016/j.isci.2021.102521
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin attenuates lipotoxicity in cardiomyocytes and protects diabetic mouse hearts by inhibiting the mTOR/HIF-1α pathway

Abstract: Canagliflozin ameliorated heart dysfunctions in HFD/ STZ-induced diabetic miceCanagliflozin inhibited lipotoxicity in palmitic acid-induced HL-1 cardiomyocytes mTOR-HIF-1a pathway mediated lipotoxicity in cardiomyocytes Canagliflozin bound to mTOR and inhibited mTOR-HIF-1a pathway

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…In our previous experiments, we found that CAN exerts anti-inflammatory effects both in vivo and in vitro . CAN significantly attenuated lipotoxicity and inflammation in cardiomyocytes ( Sun et al, 2021 ). CAN significantly reduced IL-1β levels in the plasma and lung tissues of LPS-treated NIH mice and THP-1 cells stimulated by LPS ( Xu et al, 2018 ; Niu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous experiments, we found that CAN exerts anti-inflammatory effects both in vivo and in vitro . CAN significantly attenuated lipotoxicity and inflammation in cardiomyocytes ( Sun et al, 2021 ). CAN significantly reduced IL-1β levels in the plasma and lung tissues of LPS-treated NIH mice and THP-1 cells stimulated by LPS ( Xu et al, 2018 ; Niu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hypoglycemic effect, CAN is involved in a few activities that are independent of SGLT-2. Several studies and clinical trials have shown that CAN reduces the risk of cardiovascular events ( Neal et al, 2017 ; Kosiborod et al, 2018 ; Mahaffey et al, 2018 ; Sun et al, 2021 ). We previously found that CAN effectively alleviated the pathological changes in lung inflammation in LPS-treated NIH mice ( Xu et al, 2018 ; Niu et al, 2021 ) and reduced the level of IL-1β in lung tissue and plasma ( Niu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Canagliflozin (CANA) is a kind of sodium-glucose cotransporter 2 (SGLT2) inhibitor which serves as a new hypoglycemic drug that decreases glucose reabsorption in the kidneys [10]. More and more studies indicate that CANA exhibit additional activities independent of the hypoglycemic effect [11,12]. Particularly, recent evidence has highlighted the inhibitory effects of several SGLT2 inhibitors on tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Cana has also been shown to prevent carcinogenesis in mouse models of diabetes and nonalcoholic steatohepatitis-related hepatocarcinogenesis and pancreatic cancer [2][3][4]. Cana is renoprotective in mouse models of type 2 diabetes and cisplatin renotoxicity, and cardioprotective in mouse models of diabetes [5][6][7]. Additionally, Cana alleviates LPSinduced lung injury, has an anti-inflammatory effect in vivo and in vitro, and extends lifespan in male rats [8][9][10].…”
Section: Introductionmentioning
confidence: 99%